Nuclear security and Somalia - Eric Herring; Latif Ismail; Tom B. Scott; Jaap Velthuis (Taylor & Francis Group, 2020)
Scholars have not regarded Somalia as a place of relevance to thinking about nuclear security. This article gives four reasons why this perspective is not well founded. First, as the state strengthens it needs an International Atomic Energy Agency (IAEA) nuclear security regime for the control of nuclear materials. Second, it has unsecured uranium reserves that could be smuggled abroad. Third, those unsecured uranium reserves could be accessed by terrorists for use in a 'dirty' bomb. Fourth, there is evidence of past 'ecomafia' intent and planning, and possible success, in dumping radioactive waste on land in Somalia or in its territorial waters. The article proposes an innovative system of uranium ore fingerprinting, covert sensors, mobile phone reporting and surveying and evaluation capabilities that would address all four issues. The proposed system would include a low-cost method for turning any smart phone into a radiation detector to crowdsource reporting of possible nuclear materials, plus aerial and underwater drones with low cost radiation sensors.